Effects of NGF Addition on Llama (Lama glama) Sperm Traits After Cooling - Sari, Luciana M.; Zampini, Renato; Gonzalez del Pino, Francisco; Argañaraz, Martin E.; Ratto, Marcelo H.; Apichela, Silvana A. (Frontiers in Veterinary Science, 2021)
To provide new insights into the mechanisms through which seminal plasma proteins can protect sperm from damage caused during refrigeration, we evaluate the possibility that β-NGF can contribute to the improvement of sperm quality after cooling. First, β-NGF was detected in refrigerated sperm and compared with unrefrigerated sperm by western blotting of the proteins adsorbed by sperm, showing that native β-NGF is still present even 24 h after cooling only as an active form. Then, the effect of exogenous β-NGF on sperm quality after cooling was evaluated. A total of 12 ejaculates from male llamas (three ejaculates per male), were obtained by electro-ejaculation, diluted 4:1 with buffer Hepes-balanced salt solution and centrifuged at 800 × g for 8 min to remove the seminal plasma. Sperm were suspended in Tris-citrate-fructose-egg yolk diluent for a final concentration of 30 ×106/ml and cooled at 5°C for 24 h. After refrigeration, the extended sperm were equilibrated for 5 min at 37°C and divided into the following subgroups: sperm samples without treatment (control) and sperm samples supplemented with exogenous human β-NGF (10, 100, and 500 ng/ml). At 5, 30, and 60 min of incubation sperm were evaluated for sperm viability (using eosin/nigrosin stain), sperm motility and vigor (observed under light microscopy), and mitochondrial activity (using the JC-1 fluorescent marker). Vigor data were analyzed with the nonparametric Kruskal-Wallis test. The rest of the variables were analyzed with a mixed models approach. Mean comparisons were performed using Fisher's LSD test with a confidence level of 95%. A principal components analysis was performed to analyze the relationships between variables. Treatment of 24 h cooled sperm with 10 or 100 ng/ml of human β-NGF increased the percentage of total motility and vigor (p < 0.05). Besides, an incubation time of 60 min would be adequate to improve sperm quality, since all variables are positively related. The significant improvement observed in the motility and vigor of post-refrigerated sperm suggests that supplementation with exogenous β-NGF may be profitable for the improvement of cooled llama sperm.